2024
DOI: 10.31223/x5rq1v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Under-ice and open-water ecosystem metabolism in temperate water bodies

Abstract: Winter, historically a largely un-monitored season, is important and changing. There is evidence of the importance of under-ice phytoplankton in temperate lakes, but it is currently unknown if the often high winter phytoplankton biomass translates to high productivity and what influence it has on year-round lake metabolism. Winters are getting shorter, but our ability to forecast change is hindered by our limited understanding of what happens under the ice. Here, we compare under-ice and open-water rates of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 87 publications
(151 reference statements)
1
6
0
Order By: Relevance
“…Despite this unexpected relationship, other studies have found that high concentrations of ammonium can suppress algal growth rates (Glibert et al., 2016), and can lead to decreases in N‐fixing cyanobacteria (Yang et al., 2023), which often dominate FCR's phytoplankton community in summer months (Lofton et al., 2022). Light was additionally found to be a driver of GPP (Table 2), which was consistent with previous studies (Hu et al., 2015; North et al., 2023), and highlights the important role ice may play altering GPP rates in FCR (Leppäranta et al., 2012).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Despite this unexpected relationship, other studies have found that high concentrations of ammonium can suppress algal growth rates (Glibert et al., 2016), and can lead to decreases in N‐fixing cyanobacteria (Yang et al., 2023), which often dominate FCR's phytoplankton community in summer months (Lofton et al., 2022). Light was additionally found to be a driver of GPP (Table 2), which was consistent with previous studies (Hu et al., 2015; North et al., 2023), and highlights the important role ice may play altering GPP rates in FCR (Leppäranta et al., 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Second, in our analysis of the effects of winter ice cover on metabolism, we were limited by the longest ice duration observed during our study period (35 days in 2016), which was two to four months shorter than previous winter metabolism studies (Brentrup et al, 2021;Obertegger et al, 2017). Given the shorter ice cover duration in FCR, our results are inherently different from prior ice-cover studies that experienced deep snowpack on the ice that altered light penetration and GPP rates (Leppäranta et al, 2012;North et al, 2023). Third, our monitoring data did not include records for ice thickness or transparency, which would have improved understanding of the underwater light environment in the winter and subsequent effects on GPP rates (Leppäranta et al, 2012), but were logistically impossible to collect due to the danger of sampling intermittent ice conditions.…”
Section: Water Chemistry Is An Important Driver Of Gppmentioning
confidence: 84%
See 3 more Smart Citations